Romanticism and the re-Invention of modern religion : the reconciliation of German Idealism and platonic realism - Hampton, Alexander J. B. (Cambridge University Press, 2019)
Examines how early German Romanticism combined post-Kantian idealism and Platonic-Christian realism to develop a new aesthetics of religion.
Keywords: Romanticism -- Religious aspects -- Christianity -- History of doctrines -- 19th century.; Religion and literature.; Romantisme -- Aspect religieux -- Christianisme -- Histoire des doctrines -- 19e siècle.; Religion et littérature.; RELIGION -- Christian Life -- Social Issues.; RELIGION -- Christianity -- General.; Religion and literature; Romanticism -- Religious aspects -- Christianity -- History of doctrines; 1800-1899